Enhancement Performance of Bidirectional Optical Fiber Link UsingOptical Circulator (Al-Mansour Journal, 2022)
In this search, an approach has been suggested to design a bi-directional optical network to increase the data transmission through an optical cable. Ease of doubling the transmission capacity of the network can be achieved with no need to use new optical fiber cable by employing of optical circulators. Adding a new cable to a bidirectional optical fiber transmission system makes it very expensive. Optical circulators are non-reciprocating, one-directional and three port devices that are batter for bidirectional propagation of light in a single fiber. This design technique shows an interesting result in obtaining low insertion loss (around 1.6 dB), low return loss(-65 dB) and low crosstalk between two channels (around -70 dB).
Keywords: optical circulator; bi-directional optical fiber; insertion loss; crosstalk.